FAGA Administration Course : professional profile intended versus reality - Melo, Virginia Spinassé de (2019)
Identifying the profile of the graduation of business courses makes it clear if the institution has fulfilled what is expected during its trajectory: delivering to the labor market, professionals with the skills necessary for quality performance. The present research aims to analyze the intended professional profile and what was accomplished by the Administration course of the Faculty of Management Sciences of Garanhuns (FAGA). To achieve this objective, specific work was done describing the evolution of business courses in Brazil, reporting on the implementation of FAGA's business course, identifying the professional profile intended by the course and reporting the research results. The study made use of the monographic procedure method. We used a questionnaire with indicators based on the MEC Undergraduate Course Evaluation Instrument, applied online, among 282 graduates of the FAGA Business Administration course, graduated between 2006 and 2016. It was concluded that the Management, despite its recent history, has been contributing to organizations when placed in the professional market qualified to operate in various areas. In turn, FAGA has been complying with what was proposed in its Pedagogical Political Project.